POLEMIK SEJARAH INDONESIA MASA ISLAM: KETERBATASAN SUMBER-SUMBER MASUKNYA ISLAM KE INDONESIA - Putri, Maulida; Tambunan, Elisabeth; Sihombing , Angelina; Wali Al-Khalidi , Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
There are several theories about the arrival of Islam in Indonesia. The history of Indonesia during the Islamic Middle Ages spans a relatively long period, from the arrival of Islam just before the collapse of the Hindu kingdom of Majapahit to the end of the 19th century. However, this timeframe should not be too strictly defined, as the exact date of Islam’s arrival in Indonesia remains uncertain. The purpose of this paper is to determine the precise point at which Islam entered Indonesia. The research method used is descriptive qualitative. Based on the results, it can be seen that the process of Islamization, in the true sense, began in the 15th and 16th centuries, after Islam had grown into a religious and cultural force in the archipelago. However, Islam itself clearly arrived in the country much earlier. This phenomenon is the author’s focus in explaining the arrival of Islam in Indonesia.